Excerpts from Low Season and Green Country. Issue 4 (2nd October 2018) - Johnson, Jonathan
Abstract : Jonathan Johnson's bodies of work, Low Season and Green Country, are poetic narratives featuring color photographic images made during, and in relationship to, the act of walking through urban and rural landscapes of Thailand and Costa Rica. As a mixed-race artist, the photographer uses the act of walking as a way of situating and exploring the physical spaces that exist in both of his homes in Southeast Asia, the Midwestern United States, and other temporary residencies. This method is a critique of productivism and meditates on how geography applies to fragmented space, identity, and the construction of meaning.